Antecedents and consequences of destination image of Malaysia from perspective of west Asian Tourists - Mohammed Kani, Yusuf Ahmed (2015)
One of the major concerns of the tourism industry in any country is to develop a positive image about the country globally. The basic objective of this study is to analyze the antecedents and outcomes of destination image. Specifically, the antecedents considered are cultural values, lifestyle and destination source credibility; the outcomes considered are destination attachment, destination satisfaction, and revisit intention. Projecting a positive image about a destination can be challenging if the destination had experienced major disasters. This study analyses the moderating role of perceived risk on destination image and revisit intention. The destination studied in this research is Malaysia which faced major disasters in 2014. A questionnaire-based survey was conducted and 383 tourists from five countries of West Asia participated in the survey. Structural Equation Modeling (SEM) was used to test the hypotheses. The outcome indicates that the findings of the study support the four hypotheses (H1, H2, H3, & H4).The key finding of this study is the significant contribution of the antecedents of this study to the literature on destination image. This study also considered two components of destination image: cognitive and affective. Other key findings of this study are the mediating roles of destination image, destination attachment, and destination satisfaction.